2012
DOI: 10.1007/s12539-012-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided subunit vaccine design against pathogenic Leptospira serovars

Abstract: Epitopes of Leptospira inducing CD4(+) T-cell responses by binding to human MHC molecules could critically contribute to the development of subunit vaccines for leptospirosis. Herein, we have identified unique vaccine peptides from outer membrane proteins (OMPs) common to four sequenced pathogenic Leptospira serovars through in silico reverse vaccinology technique. The OMPs were explored for probable antigens using jemboss and screened in ProPred subsequently to predict thirty HLA-DRB epitopes. The HLA-DRB epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We used proteomes of 23 virulent M. tb strains in the current study, among them M. tb_H37Rv strain was considered as a reference due to its predominant role in TB 12 . Complete proteomes were retrieved from the National Center for Biotechnology Information (NCBI), an imperative resource for enormous biological information 13 . In comparative proteomic approach, data processing was done using inhouse bash and R scripts in Linux environment for downstream dataset preparation and quantification in order to get conserved (common) proteins 14 .…”
Section: Comparative Proteomic Analysis and Dataset Preparationmentioning
confidence: 99%
“…We used proteomes of 23 virulent M. tb strains in the current study, among them M. tb_H37Rv strain was considered as a reference due to its predominant role in TB 12 . Complete proteomes were retrieved from the National Center for Biotechnology Information (NCBI), an imperative resource for enormous biological information 13 . In comparative proteomic approach, data processing was done using inhouse bash and R scripts in Linux environment for downstream dataset preparation and quantification in order to get conserved (common) proteins 14 .…”
Section: Comparative Proteomic Analysis and Dataset Preparationmentioning
confidence: 99%
“…Although RV has not been extensively applied to leptospiral genomes, to date, there are 10 reports in the literature that have used in silico genome mining towards the identification of leptospiral vaccine candidates. The RV process has been applied either completely [ 62 , 64 ] or just using the in silico analysis to select a small subgroup (<20) of proteins [ 38 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]; see Table 1 . The first report was by a group of researchers at the Butantan Institute in Brazil; they reported that approximately 20% of CDS in the L. interrogans serovar Copenhageni genome contained a signal peptide, transmembrane domains, lipoprotein sequence motifs or were orthologues of OMPs.…”
Section: Leptospiral Genomes As a Source Of Vaccine-related Informmentioning
confidence: 99%
“…The following reports used several in silico approaches to identify potential vaccine candidates; however, none of the targets was evaluated in the laboratory. An analysis of 74 OMPs that are conserved among four genomes of L. interrogans and L. borgpetersenii reported the presence of immunogenic T-cell epitopes [ 79 ]. The most prominent antigen, the cation efflux system membrane protein (CzcA), contained four immunogenic epitopes.…”
Section: Leptospiral Genomes As a Source Of Vaccine-related Informmentioning
confidence: 99%
“…A recent study in Thailand demonstrated that only the latex test could be considered cost-effective when compared to the no-antimicrobial option, and that latex test, microcapsule agglutination test, and lateral flow were still inferior to empirical treatment (7-day course of doxycycline, 100 mg bid treatment) [299]. A recent study on vaccine candidates for protection of leptospirosis successfully demonstrated LBJ_2271 as a protein candidate for further study of antigenic immune stimulation for vaccine development [300] whereas another recent study revealed that czcA and its four subunit vaccine peptides could be ideal T-cell driven efficacious vaccine against this disease [301]. Until epidemiologically-validated immune correlates are determined and discovery of vaccine candidates will likely continue to rely on the search for new virulence factors and outer membrane proteins of the organism.…”
Section: Pulmonary Leptospirosis and Hlamentioning
confidence: 99%